Implementasi Strategi Modelling The Way Untuk Meningkatkan Kemampuan Siswa Dalam Melaksanakan Shalat Wajib Pada Siswa Kelas 2 Sd 12 Ampaian Rotan - Munthe, Masrawati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
This study aims to describe the improvement of students' ability to perform obligatory prayers through the Modeling the Way strategy in grade 2 students of SD 12 Ampaian Rotan. This study uses the Action research method. Data were collected through observation, interviews, and tests or assignments, while data analysis was carried out using interactive modeling. The results of the study indicate that the application of the Modeling the Way strategy can improve the activity and ability to perform obligatory prayers in students. Learning activities from cycle I to cycle II increased in the aspect of reading the pillars of prayer increased by 21.8% from the good category to very good, the aspect of reading the conditions of prayer increased by 14.8% from the good category to very good, the aspect of reading things that invalidate prayer increased by 15.7% from the good category to very good, the aspect of prayer practice increased by 18.3% from the good category to very good. Student learning outcomes from the initial conditions to cycle II also experienced a significant increase from 7 students (28%) to 25 (100%) in the complete category.